Magmatizm riftov i skladčatych pojasov - Bogatikov, Oleg A. (Nauka, 1993)
Magmatism and geodynamics of the Great Caucasus -- Isotope investigations of the Ural and Kola alkaline provinces -- Evolution of mantle and basaltic magmatism of the intercontinental Baikal rift -- Aspects of the mantle processes